Perilaku Sosial Lansia Dalam Basuluak Pada Tarekat Naqsyabandiyah Nagari Pandam Gadang kec. Gunuang Omeh Kab. Lima puluh kota - Syafitri, Meidita (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2023)
The background of this research is because of the social behavior of the elderly when carrying out basuluak activities which are carried out starting 10 days before the Holy Month of Ramadan. The social behavior of the elderly is an actualization of the teachings of the Naqsyabandiyah Order which carry out actions or behaviors that are in accordance with the guidance of Rasulullah SAW.This research is a type of descriptive qualitative research. This study had informants 1 Mursyid, 1 Imam, 2 Khalifah and 3 participants of the Naqsyabandiyah Suluak Congregation Naqsyabandiyah Nagari Pandam Gadang Gunuang Omeh District through data collection techniques in the form of observation, interview and documentation techniques.This study produced data in the form of basuluak activities involving the behavior of the elderly, both individually and socially towards others. Social behavior includes respect for others, helping, social participation, and responsibility. The social behavior of the elderly in basuluak can be seen through joint prayer activities, Tarwih and Witir prayers, Friday prayers, alms, cleaning beds and cleaning mats in the surau where basuluak is. The clothes of the elderly in basuluak are wearing clothes that cover their genitals plus a white head covering that sticks out to their face to protect their eyes from bad eyes. Then the food they eat is food that is not bloody or does not come from animals (chicken, fish, beef, buffalo meat and so on). with the aim that their bodies do not get hot in order to keep their ablutions from being invalidated. Then the elderly in basuluak, sleep with unintentional circumstances and in a state of dhikr to Allah SWT or with reasons because they cannot be detained anymore. Then they worship starting from the obligatory prayers in congregation, the Tarwih and Witr circumcision prayers in congregation, dhikr in sir (in their hearts) and various other rituals of worship. Regarding their social behavior, the elderly in basuluak are focused on their relationship with God, but do not always forget their relationship with others. Their sympathy and concern are still there if someone among their family gets misfortune (death) and after that they have to return to continue the suluak activity again. The behavior of the elderly is always aimed at worshiping Allah alone and practicing the teachings of the Prophet Muhammad. They always forget the world and carry out social behavior that leads to closeness to Allah SWT.